Pseudosperma pamukkalense (Inocybaceae: Agaricomycetes), a new species from Turkey - Kaygusuz, Oğuzhan; Bandini, Ditte; Knudsen, Henning; Türkekul İbrahim (Phytotaxa, 2023)
A new species, Pseudosperma pamukkalense, discovered in Pinus nigra subsp. pallasiana forests is described from the Mediterranean climate zone of south-western Turkey. The novel species is recognized by the presence of pale straw to brownish yellowish pileus, mingled with reddish-brownish streaks with age, smooth to finely innately fibrillose pileus surface, whitish stipe with mainly cylindrical to clavate caulocystidia, large subphaseoliform basidiospores, and mostly narrowly to broadly clavate cheilocystidia. The description of the new species is based on morphological characters, and illustrations, line drawings and comparisons with allied species are provided. A molecular phylogenetic analysis of the internal transcribed spacer (ITS) and the nuclear 28S rRNA gene (nrLSU) regions supported the taxonomic recognition of the new species which was on a separate branch within the genus Pseudosperma.